Activation of Kagome lattice-structured Cu3V2O7(OH)2·2H2O volborthite via hydrothermal crystallization for boosting visible light-driven water oxidation. Issue 38 (20th July 2018) - Wang, Ping; Yang, Hengyan; Wang, Ding; Chen, AiYing; Dai, Wei-Lin; Zhao, Xianglong; Yang, Junhe; Wang, Xianying
Abstract : A facile hydrothermal crystallization procedure for activating the photocatalytic reactivities of volborthite mineral for water oxidation and high-concentration dye removal. Abstract : We report a feasible strategy via hydrothermal crystallization to activate Kagome lattice-structured Cu3 V2 O7 (OH)2 ·2H2 O volborthite mineral as a stable visible-light-driven photocatalyst. It was demonstrated to play a crucial role in stimulating absorption ability and photodegradation performance for the removal of methylene blue present in high concentration. In contrast, direct calcination was almost ineffective, whereas post-calcination was significantly detrimental. Moreover, the photocatalytic water oxidation activity of hydrothermally crystallizated volborthite was comparable to that of BiVO4, and it was clearly higher than those of WO3 and g-C3 N4 from aqueous NaIO3 solution. By further in situ decoration with an optimum amount of CoO x cocatalysts ( i.e., 2 wt%), the oxygen evolution rate of volborthite was greatly enhanced, and it was 1.6-fold, 1.8-fold and 2.9-fold higher than those of BiVO4, WO3 and g-C3 N4, respectively. The importance of hydrothermal crystallization can be elucidated in terms of water-Kagome lattice structure interactions involving built-in intrinsic electric field and formation of single hydrogen bonds.